Implementation of Electronic Medical Records and its Implications for the Effectiveness of Health Services in Indonesia: Narrative Review - Hansen, Leonardo; Oktamianti, Puput (Jurnal Health Sains, 2025)
Digitizing the health system through the implementation of Electronic Medical Records (RME) is one of the strategic steps in improving the effectiveness of health services in Indonesia. RME enables digital recording, management, and access of patient medical data, replacing manual systems that are less efficient and error-prone. This article aims to narratively review the literature that discusses the implementation of RME and its impact on the effectiveness of health services in Indonesia. The study was conducted through a narrative review approach utilizing data from various scientific articles obtained through databases such as Google Scholar and Scopus. Article selection was carried out based on certain inclusion and exclusion criteria, with a publication range of 2020–2025. The results of the review of six articles show that RME contributes positively to improving operational efficiency, documentation quality, interprofessional coordination, and patient safety. RME speeds up the service process, minimizes medical errors, and supports more accurate clinical decision-making. However, the implementation of RME also faces challenges such as limited technology infrastructure, data security issues, and the readiness of human resources that still varies. The implementation of RME in Indonesia has a significant impact on the effectiveness of health services. To maximize its benefits, strong regulatory support, ongoing training, and the development of an integrated and user-friendly system are needed.